SMM behaviour and magnetocaloric effect in heterometallic 3d–4f coordination clusters with high azide : metal ratios12. Issue 45 (1st November 2017) - Schmidt, Sebastian F. M.; Merkel, Marcel P.; Kostakis, George E.; Buth, Gernot; Anson, Christopher E.; Powell, Annie K.
Abstract : We present the synthesis and characterization of heterometallic compounds with a very large azide to metal ratio and fascinating magnetic properties. Abstract : We present the synthesis and characterization of heterometallic compounds with a very large azide to metal ratio. Their interesting structures give rise to fascinating magnetic properties.